First record of Spinetail Devil Ray, Mobula japanica (Müller & Henle 1841) from the Gulf of Antalya - Gokoglu, Mehmet; Teker, Serkan (Universitas Malikussaleh, 2022)
On 11 October 2019, one specimen of spinetail devilray Mobula japanica (Müller and Henle, 1841) was caught inadvertently by a commercial fisherman at a depth of approximately 25 m off the Gulf of Antalya. One specimen was examined in detail. M. japanica was recorded for the first time in the Gulf of Antalya.Keywords: Mobula japanica, spinetail devil ray, by-catch, Gulf of Antalya